Draft Annual Plan 2011-2012 Volume-III Government of Sikkim - Planning Commission (Planning Commission, 2011)
In keeping with the emphasis of the State Government, the Department has been making every effort towards promotion of Art & Culture through its ongoing activities like workshops, kavi-sammelans, competition, fairs and festivals and Inter-State Cultural Exchange programmes. The preservation and conservation of old and traditional buildings, structures and places having historical and cultural importance, heritage sites are also given due priority. Similarly Archaeology, Archives and establishment of Museum is another important area that the Department has been concentrating on in the recent years.
Development Planning, Economic Reforms & North - Eastern Council Affairs Department Government of Sikkim